Stathmin recruits tubulin to Listeria monocytogenes-induced actin comets and promotes bacterial dissemination - Costa, AC (2018)
The tubulin cytoskeleton is one of the main components of the cytoarchitecture and is involved in several cellular functions. Here, we examine the interplay between Listeria monocytogenes (Lm) and the tubulin cytoskeleton upon cellular infection. We show that non-polymeric tubulin is present throughout Lm actin comet tails and, to a less extent, in actin clouds. Moreover, we demonstrate that stathmin, a regulator of microtubule dynamics, is also found in these Lm-associated actin structures and is required for tubulin recruitment. Depletion of host stathmin results in longer comets containing less F-actin, which may be correlated with higher levels of inactive cofilin in the comet, thus suggesting a defect on local F-actin dynamics. In addition, intracellular bacterial speed is significantly reduced in stathmin-depleted cells, revealing the importance of stathmin/tubulin in intracellular Lm motility. In agreement, the area of infection foci and the total bacterial loads are also significantly reduced in stathmin-depleted cells. Collectively, our results demonstrate that stathmin promotes efficient cellular infection, possibly through tubulin recruitment and control of actin dynamics at Lm-polymerized actin structures.